Les jardins urbains de Séville - Raúl Puente Asuero (Revue d'ethnoécologie)
The traditional landscape of historical gardens of Seville has met replaced during the 20th century for an authentic "urban kaleidoscope" of residential zones and infrastructures of transport. From 1983 the association Comité Pro-Parque Educativo Miraflores decided to occupy an immense dump of 90 has and to transform this lot degraded in a park with the idea of improving these peripheral neighborhoods of the city. After three decades, the neighbors of the Miraflores Park have been involved actively in the improvement of the city claiming and assuming the management of social programs.Nowadays, in the current context of multi-crisis and as mechanism of response of the population, there is taking place an exponential growth of the urban gardens in Spain with a welfare vocation, of self-consumption, of guarantor of the sovereignty and the food safety and as social resource for disadvantaged families.Many urban gardens have been still the model initiated by the Miraflores Park and all has as common denominator that they are public alive spaces that strengthen the social fabric of the cities. Likewise, the urban gardens are helping to recover a few cultural values associated with the rural way that seemed to be forgotten.Nevertheless, in this context of garden effervescence, little or very little there has done the public administration (city councils, regional government and national government) that, once again, is late to the movement that comes from the street.